Applying FCM to predict the behaviour of loyal customers in the mobile telecommunications industry. (2nd January 2020) - Rizomyliotis, Ioannis; Poulis, Athanasios; Apostolos, Giovanis; Konstantoulaki, Kleopatra; Kostopoulos, Ioannis
ABSTRACT: Using empirical data from the Kuwaiti mobile telecommunications sector, this study models a fuzzy cognitive map (FCM) to investigate the reciprocal effects of customer loyalty and its antecedents in an emerging market context. This study investigates the effect of perceived service quality, perceived service value and brand equity on customer loyalty and the simultaneous analysis of the reverse causality of these variables. Data pertaining to 350 subscribers were analysed. According to the results, the model reaches the equilibrium when brand equity and customer loyalty are increased and reach an optimal level. Based on these findings, the authors provide implications for managers in the mobile telecom industry.